Biocontrol and plant growth promotion by combined Bacillus spp. inoculation affecting pathogen and AMF communities in the wheat rhizosphere at low salt stress conditions - Ji, Chao; Chen, Zhizhang; Kong, Xuehua; Xin, Zhiwen; Sun, Fujin; Xing, Jiahao; Li, Chunyu; Li, Kun; Liang, Zengwen; Cao, Hui (Frontiers in Plant Science, 2022)
Applying plant growth-promoting rhizobacteria (PGPR) improves the efficiency of soil-borne disease control and is considered a sustainable practice. However, the effect of PGPR on the fungal community, especially pathogenic fungi and arbuscular mycorrhizal fungi (AMF), remains unclear. In this study, we examined the effects of a compound microbial agent (consisting of Bacillus subtilis HG-15 and Bacillus velezensis JC-K3) on the incidence and yield of wheat under low salt stress, as well as compared the diversity and community composition of the rhizosphere fungal and AMF communities of wheat in the CK (not inoculated bacterial agent) and BIO (inoculated with a bacterial agent) groups. Chlorophyll relative content (SPAD), net photosynthesis rate (Pn), transpiration rate (Tr), leaf water use efficiency (WUEL), grains per spike and wheat yield in the BIO group increased more than in the CK group. The number of diseased plants and disease incidence was observed to be reduced. The relative efficacy reached 79.80%. We classified 1007 fungal operational taxonomic units (OTU) based on Miseq sequencing data: 11 phyla, 173 families, 319 genera, and 521 species. Fifty-four OTUs were classified from the AMF effective sequences, including 1 phylum, 3 families, 3 genera, and 17 species. The inoculation of bacterial agents reduced the relative abundance of pathogen genera such as Gibberella, Fusarium, Cladosporium, and Alternaria in wheat rhizosphere. It increased the relative abundance of AMF species such as Glomus-group-B-Glomus-lamellosu-VTX00193, Glomus-viscosum-VTX00063, and Glomus-Glo2-VTX00280. In addition, pH, EC, exchangeable K, available N, total N, organic matter, and olsen P were the main driving forces for shaping wheat rhizosphere fungi. The pH value was positively correlated with the relative abundance of fungal communities in soil, especially Gibberella, Cladosporium, Fusarium, and Alternaria. In summary, inoculation with Bacillus subtilis HG-15 and Bacillus velezensis JC-K3 affected wheat yield, incidence, rhizosphere soil chemical properties, rhizosphere fungi, and AMF fungal diversity and community. The findings may provide a theoretical foundation and strain support for constructing efficient PGPR-community and clarifying its mechanism of pathogenic bacteria inhibition.